Role of OSGIN1 in mediating smoking-induced autophagy in the human airway epithelium. Issue 7 (3rd July 2017) - Wang, Guoqing; Zhou, Haixia; Strulovici-Barel, Yael; Al-Hijji, Mohammed; Ou, Xuemei; Salit, Jacqueline; Walters, Matthew S.; Staudt, Michelle R.; Kaner, Robert J.; Crystal, Ronald G.
ABSTRACT: Enhanced macroautophagy/autophagy is recognized as a component of the pathogenesis of smoking-induced airway disease. Based on the knowledge that enhanced autophagy is linked to oxidative stress and the DNA damage response, both of which are linked to smoking, we used microarray analysis of the airway epithelium to identify smoking upregulated genes known to respond to oxidative stress and the DNA damage response. This analysis identified OSGIN1 (oxidative stress induced growth inhibitor 1) as significantly upregulated by smoking, in both the large and small airway epithelium, an observation confirmed by an independent small airway microarray cohort, TaqMan PCR of large and small airway samples and RNA-Seq of small airway samples. High and low OSGIN1 expressors have different autophagy gene expression patterns in vivo. Genome-wide correlation of RNAseq analysis of airway basal/progenitor cells showed a direct correlation of OSGIN1 mRNA levels to multiple classic autophagy genes. In vitro cigarette smoke extract exposure of primary airway basal/progenitor cells was accompanied by a dose-dependent upregulation of OSGIN1 and autophagy induction. Lentivirus-mediated expression of OSGIN1 in human primary basal/progenitor cells induced puncta-like staining of MAP1LC3B and upregulation of MAP1LC3B mRNA and protein and SQSTM1 mRNA expression level in a dose and time-dependent manner. OSGIN1-induction of autophagosome, amphisome and autolysosome formation was confirmed by colocalization of MAP1LC3B with SQSTM1 or CD63 (endosome marker) and LAMP1 (lysosome marker). Both OSGIN1 overexpression and knockdown enhanced the smoking-evoked autophagic response. Together, these observations support the concept that smoking-induced upregulation of OSGIN1 is one link between smoking-induced stress and enhanced-autophagy in the human airway epithelium.